Picture Reading and Scaffolding Strategies on Reading Fluency of Children with Dyslexia - Unimuke, Felicia Akpana; Ikwen, Emmanuel Umiuya; Ogunjimi, Blessing Etukudo; Egbe, Isu Michael; Akin-Fakorede, Oluwaseun Omowumi; Enidiok, Mary Sunday; Odey, Michael Obi; Ogar-Ikwen, Theresa Andorshiye; Ewa, Victoria Zake; James, Daniel Daniel; Olofu, Precilla Alu; Edom, Paulina Iye; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
The experimental study investigated the effects of picture reading and scaffolding strategies on the reading fluency of children with dyslexia in the Ogoja Education Zone of Cross River State. A factorial matrix pretest-posttest control experimental design was used in the study. A sample of thirty children who exhibited signs of dyslexia in the study area were purposively selected and assigned to control and experimental groups. Four null hypotheses were formulated to guide the study. Picture Reading (PR) and Scaffolding strategies were used as treatment packages. The duration of the study was six consecutive weeks. Pre-test and post-test data were collected using the Reading Proficiency of Children with Dyslexia Package (RPCDP). Data were analyzed using Analysis of Covariance (ANCOVA) to determine the effect of the treatment on the experimental group. Findings revealed that children exposed to picture reading and scaffolding strategies performed better, and their reading fluency was improved. The study also revealed that gender has no effect on the reading fluency of children with dyslexia. It was concluded and recommended that the use of pictures and images should be encouraged in the process of teaching reading, as children learn fast and better with what they see and are allowed to practice on their own.